Democratisation in the South African parliamentary Hansard? A study of change in modal auxiliaries. (May 2020) - Kotze, Haidee; van Rooy, Bertus
Abstract: Parliaments are a primary site where political and social democratisation can be seen in action, making parliamentary discourse, as represented in the Hansard of Commonwealth countries, a particularly relevant source of linguistic evidence for the effects of democratisation on language change. South Africa offers an exemplary case of social change which may influence language use. This paper first outlines the historical trajectory of democratisation in the South African parliament. It subsequently sets out to explore patterns of mutual influence between these socio-political changes and changes in the use of English modal auxiliaries of obligation and necessity in a specialised corpus consisting of the South African parliamentary Hansard, sampled at 10-year intervals from 1900 to 2015. The South African data are compared with data from comparable diachronic corpora of the Australian and British Hansard. We interpret our findings in the frame of possible linguistic democratisation aligned with social and political democratisation. Changes in the frequencies of must, should, HAVE to, (HAVE) got to, need and NEED to across the three varieties are reported first, before turning to the semantics of the modals must, should, HAVE to and NEED to . Our findings demonstrate how ongoing language change is receptive to local contexts of use. The data from the South African, Australian and British Hansards show signs of changes similar to the overall changes observed across native varieties of English, such as the gradual decline in the frequency of all modals together, and the increase in frequency of quasi-modals. However, where the British and Australian Hansards match the global trends more closely, the South African data show more signs of deviations from these patterns, which appear to be closely associated with not only demographic changes in parliament, but also the dynamics of conciliation in the broader framework of political democratisation and new patterns of political contestation. Highlights: Parliamentary Hansard records are an ideal testing ground to study democratisation. South African Hansard does not show long-term decline in deontic uses of modals. Language change in modals are closely tied to shifts in political power. Modal use with direct second-person addressees reflect colloquialisation. Democratisation does not always co-occur with avoidance of face-threatening usage.